113k views
3 votes
D + 4(d + 6) = -11 *

1 Answer

4 votes

Hey there!


d+4(d+6)=-11

Let's simplify both sides of the equation:


d+4(d+6)=-11

Now let's distribute:


d+(4)(d)+(4)(6)=-11\\d+4d+24=-11

Now combine like terms:


(d+4d)+(24)=-11\\5d+24=-11

Subtract 24 from both sides:


5d+24-24=-11-24\\5d=-35

Now divide both sides by 5:


(5d)/(5)=(-35)/(5)

In order to get our answer, we need to simplify by dividing -35 and 5:


(-35)/(5) =-7\\d=-7

Hope this helps!


AT2309

User Abhishek Honrao
by
5.3k points